2006
DOI: 10.1186/1472-6882-6-16
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of complementary and alternative medicine use by children and adolescents attending the University Hospital of Wales

Abstract: BackgroundA high prevalence of CAM use has been documented worldwide in children and adolescents with chronic illnesses. Only a small number of studies, however, have been conducted in the United Kingdom. The primary aim of this study was to examine the use of CAM by children and adolescents with a wide spectrum of acute and chronic medical problems in a tertiary children's hospital in Wales.MethodsStructured personal interviews of 100 inpatients and 400 outpatients were conducted over a 2-month period in 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
74
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 38 publications
9
74
2
2
Order By: Relevance
“…11 Similarly, poor communication between patients and health care professionals regarding herbal product use was also reported by other studies. 14,19,20 Respondents using herbal medicines without informing the treating physician may have to bear the brunt of serious clinical implications due to the possible herb-drug interactions. It has been found that herbal products interact or interfere with the normal pharmacology of some drugs with potentially fatal consequences.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similarly, poor communication between patients and health care professionals regarding herbal product use was also reported by other studies. 14,19,20 Respondents using herbal medicines without informing the treating physician may have to bear the brunt of serious clinical implications due to the possible herb-drug interactions. It has been found that herbal products interact or interfere with the normal pharmacology of some drugs with potentially fatal consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on CAM use in asthma showed fairly high prevalence rates of CAM use among children (Braganza, Ozuah, & Sharif, 2003;Crawford, Cincotta, Lim, & Powell, 2006;Mazur, DeYbarrondo, Miller, & Colasurdo, 2001;Reznik, Ozuah, Franco, Cohen, & Motlow, 2002;Shenfield, Lim, & Allen, 2002) yet the results of studies on CAM therapies do not generally support their efficacy in treating asthma (Angsten, 2000;Bielory, 2004;Bielory, Russin, & Zuckerman, 2004;Blazek-O'Neill, 2005;Gardnier & Wornham, 2000;Graham & Blaiss, 2000;Gyorik & Brutsche, 2004;Heimall & Bielory, 2004;Markham & Wilkinson, 2004). CAM prevalence rates (lifetime and current) among children with asthma range from 52% to 89% (Braganza et al; Mazur et al; Reznik et al; Shenfield et al).…”
mentioning
confidence: 99%
“…In the general pediatric population, studies show that the majority of parents do not disclose CAM use to their child's HCP (Cala, Crismon, & Baumgartner, 2003;Crawford et al, 2006;Heuschkel et al, 2002;Lanski, Greenwald, Perkins, & Simon, 2003;Madsen et al, 2003;Ottolini et al, 2001;Pitetti, Singh, Hornyak, Garcia, & Herr, 2001;Sawni-Sikand, Schubiner, & Thomas, 2002;Spigelblatt & Laine-Ammara, 1994;Wilson & Klein, 2002). The most frequently reported barriers to CAM disclosure, among the general population as well as families with children, were a feeling that the HCP did not need to know about CAM use, fear of a negative response from the HCP, and the HCP did not ask (Prussing, Sobo, Walker, Dennis, & Kurtin, 2004;Robinson & McGrail, 2004;Shaw, Thompson, & Sharp, 2006).…”
mentioning
confidence: 99%
“…International studies estimate the prevalence of CAM use in the paediatric ASD population to be between 35% and 95% [9,15,17], which compares with rates of between 10% and 30% amongst children in the general population [18][19][20][21]. Studies have reported a variety of CAM used by children with ASD, with the most commonly reported being biologicallybased products such as dietary supplements, vitamins, minerals, natural and herbal remedies [22,23].…”
Section: Doi: 107243/2054-992x-1-4mentioning
confidence: 99%